(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, taboos and vulgarisms are interpreted as means vivid stylistics which create expressiveness in the artistic text. As a rule, tabu and vulgarisms, which are not related to the belles-lettres, are studied as the means of expression of the author’s individual style, proved by commenting on the example of Farida Afruz’s poetic works.